2019
DOI: 10.1002/gps.5124
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation in mild cognitive impairment due to Parkinson's disease, Lewy body disease, and Alzheimer's disease

Abstract: Background Inflammation appears to play a role in the progression of neurodegenerative diseases. However, little is known about inflammation during early stages of cognitive decline or whether this differs in different disease groups. We sought to investigate this by assessing the inflammatory profile in patients with Parkinson disease with the early stages of cognitive impairment (PD‐MCI), patients with prodromal Alzheimer disease (MCI‐AD), prodromal Lewy body disease (MCI‐LB), and controls. Methods We obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 30 publications
0
29
0
Order By: Relevance
“…In line with this, inflammatory biomarkers were recently examined in studies of Rapid Eye Movement (REM) Behavior Disorder (RBD) patients. 75,76 There is some circumstantial evidence from studies of blood cytokines, which suggest that these are higher in early disease and decline with time, 77 as well as some evidence that blood lymphocytes recognizing α-synuclein antigens can be detected early. Stokholm et al 78 have observed increased PK 11195 binding in subjects with RBD.…”
Section: Question 8: When Does Inflammation Begin In Pd?mentioning
confidence: 99%
“…In line with this, inflammatory biomarkers were recently examined in studies of Rapid Eye Movement (REM) Behavior Disorder (RBD) patients. 75,76 There is some circumstantial evidence from studies of blood cytokines, which suggest that these are higher in early disease and decline with time, 77 as well as some evidence that blood lymphocytes recognizing α-synuclein antigens can be detected early. Stokholm et al 78 have observed increased PK 11195 binding in subjects with RBD.…”
Section: Question 8: When Does Inflammation Begin In Pd?mentioning
confidence: 99%
“…Serum high sensitivity Creactive protein (hsCRP) was assayed on the Siemens Advia 2400 Chemistry analyser (Siemens Healthcare Diagnostics, Frimley, UK) 44 . Serum cytokines were measured using Meso Scale Discovery (MSD) V-PLEX sandwich immunoassays 45,46 , and plates read on an MSD QuickPlex SQ 120, as in a previous study conducted in our laboratory 47,48 . MSD Pro-inflammatory Panel 1 (human) kit was used for the measurement of IFN-γ, IL-1β, IL-2, IL-4, IL-6, IL-8, IL-10, IL-12p70, IL-13, and TNF-α, and a custom Cytokine Panel 1 (human) kit was used for the measurement of IL-7, IL-17 A and vascular endothelial growth factor VEGF-A.…”
Section: Biomarkers Of Peripheral Inflammationmentioning
confidence: 99%
“…In ammation plays a vital role in neurodegenerative diseases [51,59], such as Alzheimer's disease [60], dementia with Lewy bodies [61], Wilson's disease [62], Parkinson's disease [63], multiple sclerosis [64]. Serum CHE activities is closely related to the in ammation and is involved in many pathophysiological processes of nervous system diseases [65].…”
Section: Discussionmentioning
confidence: 99%